Not just money: what mothers value in conditional cash transfer programs in India - David Bishai; Krishna D Rao; Shivani Kachwaha; Avril Kaplan (BMJ Global Health)
Introduction Conditional cash transfers (CCTs) have become an important policy tool for increasing demand for key maternal and child health services in low/middle-income countries. Yet, these programs have had variable success in increasing service use. Understanding beneficiary preferences for design features of CCTs can increase program effectiveness.Methods We conducted a Discrete choice experiment in two districts of Uttar Pradesh, India in 2018 with 405 mothers with young children (<3 years). Respondents were asked to choose between hypothetical CCT programme profiles described in terms of five attribute levels (cash, antenatal care visits, growth-monitoring and immunisation visits, visit duration and health benefit received) and responses were analysed using mixed logit regression.Results Mothers most valued the cash transfer amount, followed by the health benefit received from services. Mothers did not have a strong preference for conditionalities related to the number of health centre visits or for time spent seeking care; however, service delivery points were in close proximity to households. Mothers were willing to accept lower cash rewards for better perceived health benefits—they were willing to accept 2854 Indian rupees ($41) less for a programme that produced good health, which is about half the amount currently offered by India’s Maternal Benefits Program. Mothers who had low utilisation of health services, and those from poor households, valued the cash transfer and the health benefit significantly more than others.Conclusion Both cash transfers and the perceived health benefit from services are highly valued, particularly by infrequent service users. In CCTs, this highlights the importance of communicating value of services to beneficiaries by informing about health benefits of services and providing quality care. Conditionalities requiring frequent health centre visits or time taken for seeking care may not have large negative effects on CCT participation in contexts of good service coverage.